Kinetics and Adsorption Efficiency of Fe(III) by Fe-IIP Adsorbent for Water Remediation - Surya, Felisa Nadia Oktavira Putri; Basukiwardojo, Maria Monica Sianita (Pendidikan Kimia FKIP Universitas Jambi, 2025)
Iron (Fe) is an essential metal that plays a vital role in various biological and environmental processes. However, excessive concentrations of Fe, particularly in the form of Fe(III), can cause toxic effects, disrupt aquatic ecosystems, and pose serious risks to human health. This study aims to develop a selective adsorbent based on an Fe(III)-imprinted polymer (Fe(III)-IIP) for removing Fe(III) contamination from water. The Fe(III)-IIP was synthesized through precipitation polymerization using Fe(NO3)3, EDTA, MAA, EGDMA, and BPO as the main components. FTIR spectroscopy confirmed the presence of Fe–O functional groups and the successful removal of template ions. SEM analysis revealed a porous surface morphology with a uniform particle distribution, supporting enhanced adsorption capacity. Adsorption experiments were performed at contact times ranging from 30 to 180 minutes to determine the optimum condition. The results showed that adsorption efficiency increased with contact time, reaching equilibrium at 30 minutes with an adsorption capacity of 4.43 mg g-1, consistent with a pseudo-second-order (PSO) kinetic model. These findings demonstrate that Fe(III)-IIP is an effective adsorbent for treating Fe(III)-contaminated water. Keywords: Adsorption, Fe(III), IIP, Contact time